Discovering Cerebral Ischemic Stroke Associated Genes Based on Network Representation Learning - Liu, Haijie; Hou, Liping; Xu, Shanhu; Li, He; Chen, Xiuju; Gao, Juan; Wang, Ziwen; Han, Bo; Liu, Xiaoli; Wan, Shu (Frontiers in Genetics, 2021)
Cerebral ischemic stroke (IS) is a complex disease caused by multiple factors including vascular risk factors, genetic factors and environment factors, which accentuates the difficulty in discovering corresponding disease-related genes. Identifying the genes associated with IS is critical for understanding the biological mechanism of IS, which would be significantly beneficial to the diagnosis and clinical treatment of cerebral IS. However, existing methods to predict IS-related genes mainly initiated from the hypothesis of guilt-by-association. These methods cannot capture the global structure information of the whole protein-protein interaction (PPI) network. Inspired by the success of network representation learning (NRL) in the field of network analysis, we apply NRL to the discovery of disease-related genes and launch the framework to identify the disease-related genes of cerebral IS. The utilized framework contains three main parts: capturing the topological information of the PPI network with NRL, denoising the gene feature with the participation of a stacked autoencoder, and optimizing a support vector machine (SVM) classifier to seek out IS-related genes. Superior than the existing methods on IS-related gene prediction, our framework presents more accurate results. The case study also shows that the proposed method can identify IS-related genes.